The melody lingers on : [large type] a novel - Clark, Mary Higgins (Thorndike Press large print basic series., 2015)
Parker Bennett has been missing for two years. He dropped out of sight-- on a sailboat in the Caribbean-- just before it was discovered that the $5 billion dollars in the fund he had been managing had vanished. Lane Harmon, assistant to an upscale interior designer, is working on his wife's townhouse. Gradually, Lane finds herself drawn to Eric, the Bennetts' son, who is determined to prove that his father is not guilty. Lane doesn't know that the closer she gets to the Bennetts, the more she puts her life-- and her daughter's life-- in jeopardy.